(untitled) (Indian Journal of Child Health, 2019)
Background: Diphtheria is a vaccine-preventable deadly disease affecting the children. It may cause complications and even death if not detected early. Diphtheria still continues to be reported from many regions of India despite extensive vaccine coverage. Objective: The objective of the study was to assess the clinical presentation, complications, and outcome of diphtheria. Materials and Methods: This hospital-based prospective study was conducted from August 2017 to June 2019 in a hospital of South India. All diphtheria cases admitted during this period were included in the study and their clinical presentations, complications, and outcome were recorded. Results: A total of 93 children were studied; of them, 92 children improved and discharged while 1 (1.06%) child died of respiratory obstruction due to laryngeal edema. Diphtheria was more common in 6–10 years age group and in season between October and January. A total of 4 (4.2%) children had sinus bradycardia, 8 (8.4%) myocarditis, 10 (10.6%) palatal palsy, and 3 (3.2%) children had laryngeal edema. Conclusion: Diphtheria is a significant cause of morbidity and mortality in unimmunized and partially immunized children even in the present era.